Does clinic-based education have a sustainable impact on asthma patient awareness?. Issue 1 (1st January 2019) - Zarmouh, Anas
ABSTRACT: Introduction : Asthma patient education is an essential component of asthma management, just as inhaler treatment adherence and inhaler technique education. These issues face challenges in the developed world communities and the literature demonstrates data of various validity supporting the need for educational activities. However, communities with poor health-care facilities and low socioeconomic status have seen little or no effort to tackle this challenging area of research. Methods : This interventional study aims to impact on sustained asthma awareness with clinic-based asthma patient education. The quasi-experiment recruited asthma patients from achest clinic within apoor healthcare system at desperate economic and political times. The educational intervention consisted of an educational video, posters and leaflets, in addition to the doctor's clinic encounter and inhaler technique education by clinic nurse. Results : 24 patients of the initially recruited 87 patients were re-assessed 4 to 12 weeks later, on the impact of the educational activity on certain asthma awareness parameters. Patients' awareness of their diagnosis of asthma did not improve despite the educational activity with p= 0.141. However, there was asignificant improvement with the awareness of patients for the need of long-term inhalers (p = < 0.0001), adherence to inhaler treatment (p = < 0.0001) and correct use of inhaler (p = < 0.021). Discussion & Conclusion : The study supports the feasibility and efficacy of asthma patient education in poor health-care circumstances at basic levels of asthma knowledge, adherence and inhaler technique. This interventional study is unique in the circumstances it was carried out under. Limitations include the large number of dropouts.